Design impacts of citizen science. A comparative analysis of water monitoring projects - Kirschke, Sabrina; Bennett, Christy; Ghazani, Armin Bigham; Kirschke, Dieter; Lee, Yeongju; Loghmani Khouzani, Seyed Taha; Nath, Shuvojit (Frontiers in Environmental Science, 2023)
Citizen science is often promoted as having the capacity to enable change – from increasing data provision and knowledge product development, via behavioral change of citizens, to problem-solving. Likewise, researchers increasingly emphasize the role of project design in initiating these changes through citizen science. However, respective claims are mostly based on single case studies and reviews, calling for a systematic comparative approach to understanding the effects of project design on change. Based on a survey of 85 water-related citizen science projects from 27 countries, we analyze the comparative effects of literature-based design principles on project impacts. Factor analysis first reveals three key impact factors which are ‘Data output’, ‘Citizen outcome’, and ‘Impact chain’. Regression analysis then shows that these impact factors are significantly influenced by several design factors, amongst which motivational factors are most prominent. The analysis also shows that design factors are most important for ‘Impact chain’, followed by ‘Citizen outcome’, and ‘Data output’. While design factors only partly explain the overall project effects, the regression results are rather stable and significant when including other potential influencing factors like project responsibility and funding. In sum, the results provide an empirically substantiated and differentiated understanding of citizen science impacts and how these are influenced by project design.